2019
DOI: 10.1111/os.12567
|View full text |Cite
|
Sign up to set email alerts
|

Higher concentration of serum C‐terminal cross‐linking telopeptide of type I collagen is positively related with inflammatory factors in postmenopausal women with H‐type hypertension and osteoporosis

Abstract: ObjectiveTo investigate the changes of inflammatory factors and bone metabolism markers in postmenopausal women with H‐type hypertension and to assess the relationship between them.MethodsPostmenopausal women who were diagnosed with osteoporosis were selected as observation objects. Participants were divided into three groups: only osteoporosis group (osteoporosis group), hypertension combined with osteoporosis group (hypertension group), and H‐type hypertension combined with osteoporosis group (H‐type hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
4
0
3
Order By: Relevance
“…No effect of estradiol on these relationships was noted. Different results were presented by Chen YN et al [22], who indicated that the serum level of Ctx was positively related with both TNF-α and IL-6. In addition, they confirmed an increase in the levels of bone turnover markers Ctx and OC, and pro-inflammatory cytokines TNF-α and IL-6 in the examined postmenopausal women.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…No effect of estradiol on these relationships was noted. Different results were presented by Chen YN et al [22], who indicated that the serum level of Ctx was positively related with both TNF-α and IL-6. In addition, they confirmed an increase in the levels of bone turnover markers Ctx and OC, and pro-inflammatory cytokines TNF-α and IL-6 in the examined postmenopausal women.…”
Section: Discussionmentioning
confidence: 75%
“…These differences may result from the characteristics of the examined women which differed from those in the presented study. In a study by Chen YN et al, in which participated women diagnosed with osteoporosis and additional, accompanying diseases, including pro-inflammatory cardiovascular diseases [22].…”
Section: Discussionmentioning
confidence: 99%
“…"H-hypertension"), которая включает в себя эссенциальную гипертензию и гипергомо цистеинемию. В одной из работ оценивалась связь некоторых маркеров костного метаболизма, включая CTX-I, с маркерами воспаления и значениями МПК у женщин постменопаузального возраста [39]. В группе "Г-гипертензии" МПК в области поясничного отдела позвоночника и шейки бедренной кости была значительно ниже, чем в группе остеопороза [39].…”
Section: результатыunclassified
“…More than 75% of patients with hypertension in China have increased levels of homocysteine (Hcy), which is considered H-type hypertension when Hcy ≥ 10 µmol/L [ 1 ]. Patients with H-type hypertension are more susceptible to osteoporosis [ 2 ] and to stroke [ 3 ]. Methylenetetrahydrofolate reductase (MTHFR) plays a critical role in Hcy metabolism [ 4 ].…”
Section: Introductionmentioning
confidence: 99%